2010
DOI: 10.1001/jama.2010.920
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Myocardial Infarction, Stroke, Heart Failure, and Death in Elderly Medicare Patients Treated With Rosiglitazone or Pioglitazone

Abstract: Compared with prescription of pioglitazone, prescription of rosiglitazone was associated with an increased risk of stroke, heart failure, and all-cause mortality and an increased risk of the composite of AMI, stroke, heart failure, or all-cause mortality in patients 65 years or older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
309
2
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(327 citation statements)
references
References 35 publications
3
309
2
9
Order By: Relevance
“…This trend followed the widely-publicized 2007 U.S. Food and Drug Administration Boxed Warning that cautioned against cardiovascular adverse events including myocardial infarction with the thiazolidinedione rosiglitazone, plus concerns about increased heart failure risk with both rosiglitazone and pioglitazone. [18][19][20][21][22] Similar shifts in prescribing for other classes of medications have been observed when the FDA issued boxed warnings that were widely disseminated among physicians. 23 .…”
Section: Discussionmentioning
confidence: 62%
“…This trend followed the widely-publicized 2007 U.S. Food and Drug Administration Boxed Warning that cautioned against cardiovascular adverse events including myocardial infarction with the thiazolidinedione rosiglitazone, plus concerns about increased heart failure risk with both rosiglitazone and pioglitazone. [18][19][20][21][22] Similar shifts in prescribing for other classes of medications have been observed when the FDA issued boxed warnings that were widely disseminated among physicians. 23 .…”
Section: Discussionmentioning
confidence: 62%
“…59 Pharmacological manipulations of the molecular receptors involved in the pathways of hepatic fibrosis are promising areas of investigation, but studies to date have demonstrated discrepancies between animal and human experiences 127,130,134 and serious toxicities in some instances. 138,139 These early experiences have indicated a need for safer interventions with more precise targeting, greater understanding of the alternative fibrotic pathways that may circumvent site-specific interventions and more insight into the disease specificity of each treatment. The extracellular matrix is another therapeutic target, especially at early stages of formation before extensive cross-linkage of collagen fibrils.…”
Section: -111mentioning
confidence: 99%
“…A recent observational, retrospective, inception cohort of 227,571 Medicare patients who were treated with rosiglitazone or pioglitazone for a 12-month period and followed for up to 3 years after initiation of therapy showed rosiglitazone was associated with a higher risk of cardiovascular complications and all-cause mortality in patients 65 years or older compared with pioglitazone. 176 Rosiglitazone is currently restricted by the FDA to patients already benefiting from rosiglitazone or patients who cannot be controlled with other medications and are unwilling to use pioglitazone (http://www. fda.gov/Drugs/DrugSafety/ucm255005.htm; accession date: September 21, 2011).…”
Section: Emerging Therapeutic Agents For Diabetic Nephropathy Thiazolmentioning
confidence: 99%